Raciocínio Lógico-Matemático de um aluno do ensino fundamental com Síndrome de Asperger: dupla excepcionalidade? - Taverna, Christiane Honorato (Universidade Federal de São Carlos, 2019)
Since the late 20th century, there has been an intensifying trend of the inclusive educational system towards students belonging to the Special Education target audience (SETA), mainly in the regular educational curriculum. High Ability/ Gifted (HA/G) students belonging to this SETA group have been receiving little specialized assistance, since the number of HA/G student enrollments has not grown satisfactorily. Moreover, it was observed that dual exceptionality is less visible due to the association between HA/G and disability or disorder, and that limits its identification by the teachers. Under that premise, the primary objective of the present research was to observe a student with Asperger Syndrome and signs of a HA/G profile in logical-mathematical reasoning attending Middle School. The specific objectives were: to observe the student's performance in Math and Science activities; to describe the activities performed by the student during the observation period in Math and Science classes; and to apply the HA/G Indicator Checklist (Lista de Verificação de Indicadores de Altas habilidades/Superdotação, LIVIAH/SD). The nature of the research is observational, under a descriptive design, with outlining of the case study. The research participants were a Middle School student diagnosed with Asperger Syndrome, one Math teacher and one Science teacher of a state public school, respectively. Observations during classes were used for the data collection, within the following categories: observed classes, student demeanor during the classes, pedagogic strategies used by the teachers, student performance completing activities, student stimulation and, also, the use of a field journal and recorded classes with the consent of the student and teachers. The teachers received the HA/G Indicator Checklist (LIVIAH/SD) with 25 items, with nine indicators determined by the Science teacher and two by the Math teacher. The observation results have shown that the student revealed potential in the logical-mathematical field in comparison with his class peers; however, it wasn't possible to state that the student has a High Ability/Gifted profile, since the presented results consisted of observations performed in less than a midterm, and the content approached in Math and Science wasn't substantial enough to constitute an indication. It wasn't possible to indicate a HA/G profile using the LIVIAH/SD instrument; furthermore, there was no instrument, up to the completion of the research, that could be applied to students with suspicion of dual exceptionality (HA/G and Asperger Syndrome), and that may have interfered with the teachers' indication. Therefore, the creation of an instrument and/or assessment procedure for such dual exceptionality cases could facilitate the identification of these students.
Logical-Mathematical Reasoning of an elementary school student with Asperger Syndrome: double exceptionality?
Keywords: Educação especial; Dupla excepcionalidade; Altas habilidades; Superdotação; Síndrome de Asperger; Special education; Dual exceptionality; High ability; Gifted; Asperger syndrome; CIENCIAS HUMANAS::EDUCACAO